A Comparison of Real-Time and Endpoint Cell Viability Assays for Improved Synthetic Lethal Drug Validation. (December 2015) - Single, Andrew; Beetham, Henry; Telford, Bryony J.; Guilford, Parry; Chen, Augustine
Cell viability assays fulfill a central role in drug discovery studies. It is therefore important to understand the advantages and disadvantages of the wide variety of available assay methodologies. In this study, we compared the performance of three endpoint assays (resazurin reduction, CellTiter-Glo, and nuclei enumeration) and two real-time systems (IncuCyte and xCELLigence). Of the endpoint approaches, both the resazurin reduction and CellTiter-Glo assays showed higher cell viabilities when compared directly to stained nuclei counts. The IncuCyte and xCELLigence real-time systems were comparable, and both were particularly effective at tracking the effects of drug treatment on cell proliferation at sub-confluent growth. However, the real-time systems failed to evaluate contrasting cell densities between drug-treated and control-treated cells at full growth confluency. Here, we showed that using real-time systems in combination with endpoint assays alleviates the disadvantages posed by each approach alone, providing a more effective means to evaluate drug toxicity in monolayer cell cultures. Such approaches were shown to be effective in elucidating the toxicity of synthetic lethal drugs in an isogenic pair of MCF10A breast cell lines.